2016
DOI: 10.1016/j.jphs.2016.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane-induced pica in female rats

Abstract: We examined the effects of volatile anesthetics on pica, which can be used to assess nausea and vomiting in rats. We found that inhalation anesthesia with sevoflurane significantly induced pica in female but not male rats. Among the female rats, young rats (8 weeks old) were more susceptible to its induction than adult rats (20 weeks old) with ovariectomy or sham-surgery. Anti-emetic drugs that are used to prevent postoperative nausea and vomiting (PONV) inhibited the pica. These results suggest that sevoflura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Yamamoto et al previously showed that this pica behavior could not completely reflect gastrointestinal discomfort or emesis 14 . However, the same research group recently reported that female rats showed a greater intake of kaolin than male rats, and they determined that estrogen levels were involved in the development of kaolin pica behavior using bilaterally ovariectomized rats 15 . In humans, female sex was previously identified as the strongest PONV risk factor, 1,5 and our current and prior results 46 confirmed this (odds ratios: 14.7‐ and 7.15‐fold, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamamoto et al previously showed that this pica behavior could not completely reflect gastrointestinal discomfort or emesis 14 . However, the same research group recently reported that female rats showed a greater intake of kaolin than male rats, and they determined that estrogen levels were involved in the development of kaolin pica behavior using bilaterally ovariectomized rats 15 . In humans, female sex was previously identified as the strongest PONV risk factor, 1,5 and our current and prior results 46 confirmed this (odds ratios: 14.7‐ and 7.15‐fold, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Eating kaolin clay as a type of pica has been examined in recent animal studies as an alternative behavior to emesis 12–15 . One research group has reported the development of a rat pica model induced by cisplatin, an anticancer drug; in this model, the pattern of kaolin consumption appears to match the characteristics of cisplatin‐induced emesis in humans 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that salivation, conditioned taste aversion, gaping, secretion of vasopressin, and gastric stasis are closely associated with the development of nausea (Andrews and Horn, 2006; Cabezos et al, 2008; Parker, 2014; Scallan and Simon, 2016), but it is difficult to accurately measure these parameters in laboratory animals under physiological conditions. We previously suggested that pica behavior in rats can be used as a method to assess gastrointestinal malaise including nausea (Yamamoto et al, 2014, 2015, 2016). The amount of kaolin intake in rats is proportional to the emetogenicity in humans (Yamamoto et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One of the risk factors of chemotherapy-induced nausea and vomiting is considered to be a female sex (du Bois et al, 1992). We previously reported that female rats are more susceptible to the induction of sevoflurane-induced pica behavior than male rats (Yamamoto et al, 2016); thus, we used only female rats in a series of experiments. They were allowed free access to tap water and commercially available standard chow (CE-2, CLEA Japan, Inc., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation